Genomic discovery of EF-24 targets unveils antitumorigenic mechanisms in leukemia cells - Ajeet P. Singh; Noah Wax; James Duncan; Ana S. Fernandes; Jonathan L. Jacobs (PLoS ONE, 2025)
Curcumin, a polyphenolic compound derived from the plant Curcuma longa L., has demonstrated a wide range of therapeutic properties, including potential anticancer effects. However, its clinical efficacy is limited due to poor bioavailability and stability. To overcome these challenges, curcumin analogs like EF-24 have been developed with improved pharmacological properties. In this study, in order to improve our understanding of EF-24’s potential mechanisms of action, we used whole-transcriptome sequencing to identify genome-wide functional impacts of EF-24 treatment in leukemia cells. These results enabled the development of a testable model system for associating druggable genes with clinical disease targets related to EF-24 treatment. To develop our model of the transcriptional response to EF-24 treatment, we used four well studied model cell lines for leukemia research, specifically the chronic myeloid leukemia (CML) cell line K-562 and acute myeloid leukemia (AML) cell lines HL-60, Kasumi-1, and THP-1. Cell viability was significantly decreased in all four of these leukemia models following EF-24 treatment as compared to untreated controls. We discovered that the genes ATF3, CLU, HSPA6, OSGIN1, ZFAND2A, and CXCL8, which are associated with reduced cell viability and proliferation, were consistently upregulated in all EF-24–treated cell lines. Further analysis of the tested cell lines revealed the activation of various signaling pathways, but notably the S100 family signaling pathway was consistently activated in all four cell lines. Our results provide critical insights into the molecular underpinnings of EF-24’s antitumor efficacy against leukemia subtypes, highlighting its multifaceted impact on signaling pathways and gene networks that regulate cell survival, proliferation, and immune responses in cell line models of myeloid leukemia subtypes.